If Not Now, Then When? The Significance of CISG Ratification for Indonesia - Ratu Wulandari (Jurnal Hukum Novelty, 2021)
Introduction to The Problem: In this 21st century, Indonesia has not ratified the United Nations on Contract for the International Sales of Goods (CISG). Indonesia's government put several reasons for not becoming part of this critical convention, and the government did not see the ratification as urgent matters. However, these excuses did not find relevant anymore because more and more countries worldwide ratified the CISG, including North Korea.Purpose/Objective Study: The objective of this article is addressing the issue of Indonesia has not yet ratify the United Nations on Contract for the International Sales of Goods (CISG) despite the rise of export and import activities conducted by Indonesian enterprises.Design/Methodology/Approach: The methodology used in this article is based on the literature review of CISG, Indonesian development of CISG, and minor comparative analysis between the signatory and non-signatory countries.Findings: The ratification of CISG would provide more benefits and outweighed its disadvantages because CISG presents legal certainty to international contract law since the Indonesian Civil Code failed to address this issue. CISG ratification will also strengthen the Indonesian legal system, legal institutions, and legal practitioners.Paper Type: Research Article